Regulatory B cells: Development, phenotypes, functions, and role in transplantation. Issue 1 (27th September 2019) - Alhabbab, Rowa Y.; Nova-Lamperti, Estefanía; Aravena, Octavio; Burton, Hannah M.; Lechler, Robert I.; Dorling, Anthony; Lombardi, Giovanna
Abstract: The interest in regulatory B cells (Bregs) began in the 1970s with the evidence that B cells could downregulate the immune system by the production of "inhibitory" antibodies. Subsequently, a series of results from different studies have emphasized that B cells have antibody‐independent immunoregulatory functions. Since then, different subsets of B cells with regulatory functions and their development and mechanisms of action have been identified both in human and in animal models of inflammation, transplantation, and autoimmunity. The present review outlines the suggested pathways by which Bregs develop, describes the different subsets of Bregs with their phenotypes and function as well as their role in transplantation, highlighting the differences between human and animal studies throughout.